GLOBALIZATION IN THE NORTH AMERICAN REGION: TOWARD RENEGOTIATION OF CULTURAL SPACE - Ghosh, Ratna (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2004)
ABSTRACT. There are sharp differences in the economic, educational and political conditions among the NAFTA countries. This paper focuses on the difference in cultural and value orientations in Mexico, Canada and the United States. Education is increasingly market driven, which poses a challenge in balancing the integration of education with international standards while still maintaining distinctive cultures. A conceptual model is proposed as a constructive approach for socio-cultural integration, and its educational implications are discussed. MONDIALISATION EN AMÉRIQUE DU NORD: VERS LA RENÉGOCIATION DE L'ESPACE CULTUREL RÉSUMÉ. Les conditions économiques, pédagogiques et politiques diffèrent grandement au sein des pays de l'ALENA. Ce document met l'accent sur la différence d'orientation sur les plans de la culture et des valeurs au Mexique, au Canada et aux États-Unis. L'enseignement est de plus en plus axé sur le marché, ce qui pose le défi d'intégrer l'enseignement aux normes internationales tout en maintenant l'identité des cultures distinctes. Un modèle conceptuel est proposé comme approche constructive à l'intégration socioculturelle et ses incidences au niveau de l'enseignement sont abordées.